Public Perception of Social Media Contributions to Political Participation Processes in Delta State, Nigeria: Array - Erubami, Aghogho Joshua (Acta Universitatis Danubius. Communicatio, 2020)
The social media have become a critical component of Nigeria’s democracy, with widely acclaimed potentials for influencing public civic engagement. However, the nature and direction of such influence remains a source of debate among researchers. This study examined public perception of the contributions of social media to political participation processes in Delta State, Nigeria. It adopted the survey method using a sample of 500 respondents selected through a multistage sampling technique. A likert scale questionnaire was used to collect data which were analysed using descriptive statistics. Findings revealed that although the social media were perceived to have positively influenced Nigeria’s democracy by enhancing the flow of political information and awakening public political consciousness, the news and information being disseminated on social media platforms were noted to have increased the spate of hate speech and stoked political unease. The study recommended that citizen journalists should imbibe online responsibility and be sensitive to public needs and expectations while using any of the social media platforms for political ends.